Trans-Ned 19-Mediated Antagonism of Nicotinic Acid Adenine Nucleotide—Mediated Calcium Signaling Regulates Th17 Cell Plasticity in Mice - Mikołaj Nawrocki (MDPI AG, 2021)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is the most potent Ca2+ mobilizing agent and its inhibition proved to inhibit T-cell activation. However, the impact of the NAADP signaling on CD4+ T-cell differentiation and plasticity and on the inflammation in tissues other than the central nervous system remains unclear. In this study, we used an antagonist of NAADP signaling, trans-Ned 19, to study the role of NAADP in CD4+ T-cell differentiation and effector function. Partial blockade of NAADP signaling in naïve CD4+ T cells in vitro promoted the differentiation of Th17 cells. Interestingly, trans-Ned 19 also promoted the production of IL-10, co-expression of LAG-3 and CD49b and increased the suppressive capacity of Th17 cells. Moreover, using an IL-17A fate mapping mouse model, we showed that NAADP inhibition promotes conversion of Th17 cells into regulatory T cells in vitro and in vivo. In line with the results, we found that inhibiting NAADP ameliorates disease in a mouse model of intestinal inflammation. Thus, these results reveal a novel function of NAADP in controlling the differentiation and plasticity of CD4+ T cells.